Infrastructure of interconnected microgrids: A review - Moshammed Nishat Tasnim; Tofael Ahmed; Shameem Ahmad; GM Shafiullah (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
The microgrid (MG) cluster is one of the feasible ways to integrate large-scale renewable energy sources, address the constrained energy exchange problems, and optimize power system efficiency, resiliency, and reliability. The present power system will probably shift into a network of MGs to bring about economic gains by employing demand-supply balance. However, various factors related to interconnected MG (IMG) infrastructure, such as the diversity of IMG architecture, economic viability, integration capacity, reliability, operational flexibility, and communication and protection schemes, can create great challenges in implementing efficient and resilient IMG infrastructure. Therefore, to address this concern, different IMG infrastructures are explored and analyzed to bring out the benefits, challenges, and constraints of the presented IMG architectures in this review. Accordingly, the concepts of IMGs and potential IMG architectures based on layout, line, and interface technologies are first discussed and compared. Then, numerous factors like cost, reliability, scalability, flexibility, complexity, and efficiency that play a significant role in evaluating the performance of IMG structures are identified to present a comparative analysis among various architectural topologies. All these analyses and comparisons are expected to serve as a reference in the field of IMG infrastructure to select a suitable framework based on the necessary functionalities. This paper also provides potential challenges related to IMG architecture and recommendations for future research studies to improve IMG infrastructure and operation.